2018
DOI: 10.1016/j.drugalcdep.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing daily drivers of problem drinking among older and younger adults: An electronic daily diary study using smartphones

Abstract: Older adults may have unique daily drivers of drinking that are not fully realized in current research and intervention efforts. Addressing the growing substance-use treatment needs among this population will require identifying the unique drivers of drinking among older adults, such as boredom, when compared to younger adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…Additionally, low self-efficacy is associated with fewer health promotion behaviors among OA due to perceiving the related consequences as normal aging. A recent study found that OA with high daily commitment and confidence to not drink heavily did not reduce their daily drinking as much as their younger counterparts [62]; in other words, high motivation and self-efficacy were not as protective for OA as for younger adults.…”
Section: Motivation and Self-efficacymentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, low self-efficacy is associated with fewer health promotion behaviors among OA due to perceiving the related consequences as normal aging. A recent study found that OA with high daily commitment and confidence to not drink heavily did not reduce their daily drinking as much as their younger counterparts [62]; in other words, high motivation and self-efficacy were not as protective for OA as for younger adults.…”
Section: Motivation and Self-efficacymentioning
confidence: 93%
“…Male gender (for alcohol, marijuana, tobacco) [10,13] Female gender (for prescription drugs) [11,32] Caucasian [10,13] Age (being closer to middle age) [10,11] Less than college education [11] Physical factors Chronic pain [62] Physical disabilities or reduced mobility [5] Poor physical health status, chronic physical illness [10] Significant drug burden/polypharmacy Psychiatric factors…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrinking social networks and deaths from COVID-19 leaves many without coping resources (65). Social isolation, loneliness, death of loved ones, complicated grief, and prolonged bereavement are associated with problematic substance use and relapse both in younger and older adults, and can adversely affect mental health (17,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Bereavement and Loneliness: Lasting Effects Of The Covid-19 mentioning
confidence: 99%
“…The picture is quite different when it comes to BP, since this personality trait differentiated markedly patients with and without AC, which adds up to findings on the relationship between boredom and drinking among adolescents, young (Biolcati et al, 2016;Windle and Windle, 2018), and older adults (Kuerbis et al, 2018;Patrick et al, 2017). But differences in scores on BP subscales also reflect distinct reasons for the occurrence of boredom (Vodanovich et al, 2005).…”
Section: Discussionmentioning
confidence: 77%